Meningkatkan Hasil Belajar Pendidikan Agama Katolik dan Budi Pekerti Metode Problem Based Learning Berbantuan Media Audio Visual Fase E Kelas X SMK Negeri IV SPP-SPMA Singkawang - Giovani Rikho; Y L Sukestiyarno; Martina Murlani (Sekolah Tinggi Pastoral Kateketik (STPKat) Santo Fransiskus Assisi Semarang, 2024)
The purpose of this study was to improve the learning outcomes of Catholic students in Catholic Religion lessons in class X with the Problem Based Learning model assisted by audio visual. The type of research used is Classroom Action Research which is carried out in two learning cycles. The research subjects were 15 Catholic students in class X DKV SMK Negeri IV SPP-SPMA Singkawang. To determine the achievement of student learning outcomes, researchers used written tests as a measuring tool. Meanwhile, to determine the learning outcomes of Pancasila students' profile in the dimension of critical reasoning, observation techniques were used. The results showed an increase in student learning outcomes by using problem-based learning, both cognitive and affective. Data on student cognitive learning outcomes, in cycle I the average value was 74%. Experienced an increase in cycle II to 83%. Data from the observation of the Pancasila learner profile of the critical reasoning dimension in cycles I and II showed an increase. Where in cycle I the average value was only 71%, it increased in cycle II by 82%. So, it can be concluded that the application of the Problem based learning model assisted by audio visual can improve student learning outcomes.